Dietary and performance assessment of elite soccer players during a period of intense training - Rico-Sanz, J.; Frontera, W. R.; Mole, P. A.; Rivera, M. A.; Rivera-Brown, A.; Meredith, C. N. (International Journal of Sport Nutrition and Exercise Metabolism, 1998)
This study examined the nutritional and performance status of elite soccer players during intense training. Eight male players (age 17 ± 2 years) of the Puerto Rican Olympic Team recorded daily activities and food intake over 12 days.